PENGARUH MOTIVASI, BUDAYA ORGANISASI DAN TURNOVER INTENTION TERHADAP PRODUKTIVITAS KERJA KARYAWAN: (Studi pada Karyawan PT Bank Sumut Kantor Pusat Medan Divisi Sumber Daya Manusia) - Sarah Vera Indah Siburian; Onan Marakali Siregar (Transpublika Publisher, 2023)
This study aims to analyze how motivation, organizational culture, and turnover intention impact employee productivity (a study conducted on employees of PT Bank Sumut Medan Head Office Human Resources Division). The research design employed in this study is quantitative research with an associative approach. Sampling was conducted using the saturated sampling technique, and 41 respondents were selected as samples. Primary data for this study were obtained by distributing questionnaires directly to employees (respondents), while secondary data were gathered through literature studies. The data analysis techniques included validity tests and reliability tests. The data analysis methods encompassed classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that motivation, organizational culture, and turnover intention all have a significant impact, both individually and collectively, on employee productivity.